2011
DOI: 10.1111/j.1442-8903.2011.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Sampling indigenous ground-living beetles in a stand of non-native tree privet (Ligustrum lucidum) in New Zealand raises new management questions

Abstract: SummarySmall urban forest reserves in New Zealand have been shown to have value in conserving indigenous beetle diversity. However there is little information available on the ability of non-native vegetation areas such as tree privet to support indigenous beetle assemblages. To investigate this for one site, ground-living beetles were collected using pitfall traps over a year at a small urban forest of the invasive tree Ligustrum lucidum (tree privet) in Auckland, New Zealand. A total of 815 beetles were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Species richness of other groups of organisms, such as soil fauna (Fernandez 2018 ) and microflora (Fernandez et al 2017 ) may be also affected in different ways by changes that L. lucidum invasion generates in litter quality, soil chemistry and micro-environmental conditions. Order richness of soil fauna was similar in L. lucidum and native riparian and Serrano forest of Uruguay (Brazeiro 2018 ), and the same was true for beetle species richness in L. lucidum and native forest of Auckland city in New Zealand (Blanchon et al 2011 ). A contradictory pattern was found for spider species or morphospecies richness in Espinal forest of Entre Rios, Argentina.…”
Section: Ecological Effects Of L Lucidum Invasionmentioning
confidence: 91%
“…Species richness of other groups of organisms, such as soil fauna (Fernandez 2018 ) and microflora (Fernandez et al 2017 ) may be also affected in different ways by changes that L. lucidum invasion generates in litter quality, soil chemistry and micro-environmental conditions. Order richness of soil fauna was similar in L. lucidum and native riparian and Serrano forest of Uruguay (Brazeiro 2018 ), and the same was true for beetle species richness in L. lucidum and native forest of Auckland city in New Zealand (Blanchon et al 2011 ). A contradictory pattern was found for spider species or morphospecies richness in Espinal forest of Entre Rios, Argentina.…”
Section: Ecological Effects Of L Lucidum Invasionmentioning
confidence: 91%
“…In New Zealand, beetles have been used extensively as 'indicators' for biodiversity and conservation assessment (Hutcheson 1990;Hutcheson & Kimberley 1999;Harris & Burns 2000;Ward & Larivière 2004;Watts & Larivière 2004;Ewers et al 2007;Pawson et al 2008;Blanchon et al 2011;Leschen et al 2012). However, these studies have not examined temporal patterns.…”
Section: Introductionmentioning
confidence: 97%
“…They reported that only one-third of possum dens were in indigenous trees, and the statistical analysis indicated that indigenous tree species were less likely to be used for den sites than the most common alien tree species. Blanchon et al [13] found that an urban forest dominated by alien woody plants had 50% more species of ground beetles than a smaller, nearby urban forest dominated by indigenous plants. In contrast, bird and butterfly species richness was more diverse within and between green patches in Singapore dominated by native vegetation relative to those dominated by non-native species [14].…”
Section: Introductionmentioning
confidence: 99%